Urban Food Sharing Rules, tools and networks - Davies, Anna R. (Policy Press, 2019)
Available Open Access under CC-BY-NC licence. This book explores the history and current practice of food sharing. Illustrated by rich case studies from around the world, the book uses new empirical data to set an agenda for research and action. The book will be an important resource for researchers, policy makers and sharing innovators to explore the impacts and sustainability potential of such sharing for cities.